Seasonal Nutrient Cycling and Enrichment of Nutrient-Related Soil Microbes Aid in the Adaptation of Ramie (Boehmeria nivea L.) to Nutrient-Deficient Conditions - Wu, Shenglan; Xue, Shuai; Iqbal, Yasir; Xing, Hucheng; Jie, Yucheng (Frontiers in Plant Science, 2021)
The current used ramie (Boehmeria nivea L.) varieties are generally characterized to have a weak poor soil tolerance ability, which has caused the slow expansion or even shrinking of the ramie production. To support the future barren-tolerance breeding work, the first aim of this study is to screen tolerable materials. Based on the screened materials, a further objective is designed to explore the tolerable strategies of ramie plant to poor soil condition. The poor soil tolerance abilities between genotypes were compared based on their field performances after a long-term (8-9 years) cultivation. Results show that the variations of ramie plant performances between genotypes after a long-term cultivation are totally different with that in the establishment year. The long-term field trials indicate that genotypes of Duobeiti 1 and Xiangzhu XB have the outstanding tolerance abilities to poor soil condition. For the tolerance strategies, contributions of nutrient seasonal cycling and rhizobacteria change to the ramie’s poor soil tolerance were tested. Results show that N and P retranslocation to root at the end of the growing season helps ramie adapting to the poor soil condition. Contribution of microbial community was analyzed based on high-throughput Illumina Miseq sequencing technology. Results show that enrichment of the beneficial bacteria (mainly Bradyrhizobium, Gaiella and norank_o_Gaiellales) and reducing of the harmful fungus (mainly Cladosporium, Aspergillus) also contribute to the ramie poor soil tolerance ability.